ANALISIS PENGARUH DISKON, PROMOSI, DAN KEPERCAYAAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PADA PENGGUNA APLIKASI SHOPEE - Nila Heriter Qur’an; Satriawan Satriawan; Putri Reno Kemala Sari (Kredibel: Jurnal Ilmiah Manajemen, 2023)
This research was conducted to find out how much influence Discounts, Promotions and Consumer Trust have on Purchase Decisions for Shopee Application. The data used are primary data obtained from the distribution of questionnaires with 60 respondents. The results of this study indicate that there is a significant positive effect of discounts on purchasing decisions for STIE AMM Mataram students who use the Shopee application. There is a significant positive effect of promotion on purchasing decisions for STIE AMM Mataram students who use the Shopee application. There is a significant positive effect of Consumer Trust on purchasing decisions for STIE AMM Mataram students who use the Shopee application. There is a significant positive effect simultaneously on discounts, promotions and consumer confidence on purchasing decisions for STIE AMM Mataram students who use the Shopee application. There is a promotion that has more influence on purchasing decisions for STIE AMM Mataram students than discounts and consumer confidence. The value of the coefficient of determination (R) is 0.922 (92.2%) which means the ability of the promotional discount variable and trust in purchasing decisions to shopee application users in explaining the variation of the dependent variable is very strong